2019
DOI: 10.1093/mnras/stz3361
|View full text |Cite
|
Sign up to set email alerts
|

Are inner disc misalignments common? ALMA reveals an isotropic outer disc inclination distribution for young dipper stars

Abstract: Dippers are a common class of young variable star exhibiting day-long dimmings with depths of up to several tens of percent. A standard explanation is that dippers host nearly edge-on (i d ≈ 70 • ) protoplanetary discs that allow close-in (<1 au) dust lifted slightly out of the midplane to partially occult the star. The identification of a face-on dipper disc and growing evidence of inner disc misalignments brings this scenario into question. Thus we uniformly (re)derive the inclinations of 24 dipper discs res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 115 publications
9
56
0
Order By: Relevance
“…Dippers with nearly faceon outer disks have been found before (e.g., Ansdell et al 2016b;Scaringi et al 2016). In particular, Ansdell et al (2020) found the disk inclination distribution to be consistent with isotropic. The possible explanations they proposed include dust clouds driven by disk winds (which can determine dips in systems with inclinations as low as ∼30 • ), or misalignments between inner and outer disk (which might be caused by a substellar or planetary companion).…”
Section: Discussionsupporting
confidence: 52%
“…Dippers with nearly faceon outer disks have been found before (e.g., Ansdell et al 2016b;Scaringi et al 2016). In particular, Ansdell et al (2020) found the disk inclination distribution to be consistent with isotropic. The possible explanations they proposed include dust clouds driven by disk winds (which can determine dips in systems with inclinations as low as ∼30 • ), or misalignments between inner and outer disk (which might be caused by a substellar or planetary companion).…”
Section: Discussionsupporting
confidence: 52%
“…Dippers instead are very young, PMS stars in almost all cases with active accretion from a primordial disk and strong infrared (IR) excesses; their flux dips are generally believed to arise from dust in the primordial disk itself or possibly from dust blobs in transit from the disk toward the star. (Also see Ansdell et al 2020. )…”
Section: A Brief Discussion Of Nomenclaturementioning
confidence: 97%
“…In this paper, we present new ALMA Band 6 220 GHz continuum observations of LkCa 15 and 2MASS J16100501-2132318 (EM*StHA 123, EPIC 204630363, hereafter J1610) at unprecedented angular resolution (∼40 × 60 mas, i.e., ∼7.5 and 6 au in radius for LkCa 15 and J1610, respectively). Both objects are classical T Tauri stars hosting transition disks with resolved cavities (Piétu et al 2006;Ansdell et al 2020). Interestingly they are also classified as dippers, based on the short term variability seen in their optical light curves (Ansdell et al 2016;Rodriguez et al 2017;Alencar et al 2018).…”
Section: Introductionmentioning
confidence: 99%